Isolation, conventional and molecular characterization of Salmonella spp. from newly hatched broiler chicks - Mahmoud E. Sedeik (AMB Express, 2019)
Abstract Salmonella is an important pathogen for poultry production as well as for human due to zoonotic importance. It has more than 2600 identified serovars despite of this identification and classification of Salmonella isolates into different serovars is critical for study of incidence and surveillance. This study investigates the epidemiology and molecular characterization of Salmonella isolates in broiler chicks during 1st week of life. A total of (n = 1000) samples including liver, intestine, yolk sac, spleen and heart blood were collected from El-Gharbia, El-Behera, Kafr-Elshikh, Alexandria, Marsamatroh Provinces in Egypt and tested through bacteriological, biochemical, serological and molecular examinations. Incidence of Salmonella was demonstrated on 75 positive samples from 1000 samples and the predominance of Salmonella that isolated from internal organs of newly hatched chicks was highest from yolk sacs (10%), liver and intestines (9%) followed by the spleen (7.5%) then heart blood (2%). Serotyping of the isolated strains using slide agglutination test revealed that 24 isolates belonging to S. enteritidis (1,9,12 g.m 1,7), while, 14 isolates belonging to S. virchow (6,7 r 1,2), in addition to, 12 isolates belonging to S. typhimurium (1,4,5,12.i.1,2) and 8 isolates belonging to S. kentucky (6,8.I,z). Enterobacterial Repetitive Intergenic Consensus (ERIC) PCR revealed that two S. enteriditis isolates were identical and one isolate differ by 40%, while two S. typhimurium isolates were identical by 80% and one isolate was similar by 20% to the other two isolates, in addition, two S. virchow isolates were identical by 80% and the two S. kentucky isolates were different.